(untitled) (Economics and region, 2025)
This study focuses on harnessing blockchain’s transformative potential to address long-standing issues such as climate change, infrastructural deficiencies, corruption, and economic instability. Recognizing the agricultural sector’s role in ensuring food security and economic prosperity, this work outlines blockchain’s advantages in fostering transparency, security, and operational efficiency. The article highlights blockchain applications across various domains, including agricultural insurance, which safeguards against weather-induced risks, and supply chain management, where traceability enhances product safety and consumer confidence. Furthermore, it delves into electronic commerce, proposing decentralized platforms for secure and efficient transactions, and land registration systems that ensure immutable and transparent record-keeping. Comparative analysis with centralized systems underscores blockchain’s unique capabilities, such as decentralization and enhanced security, alongside its long-term cost benefits. Innovations such as smart contracts, e-commerce platforms, and automated management systems can significantly enhance the efficiency of agricultural businesses and ensure their sustainable development. Despite the potential, the adoption of blockchain in Ukraine faces significant barriers, such as technological accessibility and the high costs of implementation. The author emphasizes the importance of investment in infrastructure, targeted education programs for farmers, and the development of affordable solutions. Innovations like smart contracts, automated data management, and advanced agricultural platforms are presented as pivotal to achieving sustainable growth in this sector. By integrating blockchain into agriculture, this research envisions a future where the industry leverages cutting-edge technology to enhance productivity, reduce operational costs, and establish Ukraine as a leader in agricultural innovation on the global stage.